If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -12x = -120 Combine like terms: -3x + -12x = -15x -15x = -120 Solving -15x = -120 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-15'. x = 8 Simplifying x = 8
| 9(x+1)-(5x-3)=3 | | 7(10-6x)=58-6(6x+1) | | -8=-7x | | 7(x+3)-(4x-9)=8 | | 4(5+2q)=-4+5q | | -6(-1x+8)=18 | | x^2-50=-1 | | 65-34.3=x | | x-9=3x-11 | | -56=7+7x | | 9-3x=7x+19 | | 8(x+7)-(5x-9)=1 | | .37+1.1m=2.65m-1.18 | | 4x+18=34 | | 11x+5x-1=32 | | -5x-7=41-x | | 2.4=16x | | 12(1.15)= | | y*6=3.3 | | 4x^2+20x+12=x+20 | | x+6=-7x+86 | | 1/2(x+4)=1/3(3x-6) | | -3(-2x+7)=-81 | | x+31=78 | | 3-3.7(8-x)=16.5 | | 19=2a-(a+1) | | 7x-56=9-3x+5-4x | | n-40=47 | | 4y=28 | | -11-5=(5x+4) | | z-9=4 | | x^4+2x^3+1=0 |